2016
DOI: 10.4081/jlimnol.2016.1405
|View full text |Cite
|
Sign up to set email alerts
|

First observations of anthropogenic underwater noise in a large multi-use lake

Abstract: Over

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…They also have shown that seismic surveys can disrupt diurnal activity cycles which may have long term negative consequences on this species’ foraging success and fitness. Although to date, there is a gap in knowledge in terms of freshwater soundscape environments and how elevated sound levels affect fish in freshwater habitats (Bolgan et al, 2016; Linke et al, 2018; Rountree et al, 2020; Putland and Mensinger, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…They also have shown that seismic surveys can disrupt diurnal activity cycles which may have long term negative consequences on this species’ foraging success and fitness. Although to date, there is a gap in knowledge in terms of freshwater soundscape environments and how elevated sound levels affect fish in freshwater habitats (Bolgan et al, 2016; Linke et al, 2018; Rountree et al, 2020; Putland and Mensinger, 2020).…”
Section: Discussionmentioning
confidence: 99%